O uso de argumentos sobre verdade e esperança em campos científicos controversos: um estudo sobre a veiculação de pesquisas com células-tronco na mídia - Freitas, Thiago Ribeiro de (2010)
Science is a collective activity that goes beyond the boundaries of the laboratory and involves a heterogeneous network of people and elements in a constant negotiation of power. To elect stem cells as a case study, we assume that these cells are located in a controversial field. That is, issues such as stem cell research are located in the center of a convergence of opposing logics: on one hand, the subject is driven by hope, and on the other, the subject is tempered by the logic of truth. Thus, focusing on the dissemination of science in the media, we chose to analyze three media vehicles considering their differences from the audience for whom they were directed. We selected the Pesquisa FAPESP periodical because it is a means of disseminating science to researchers; the periodical Ciência Hoje due to being a form of divulgation for a common public consumer of news stemming from the science; and the journal Folha de S. Paulo as an example of media aimed at the collective public in general. Thus, we seek to understand the visibility of stem cell research in these different media sources. Through the material offered in the newspaper Folha de S. Paul, we seek to understand in a time perspective, the news about the technique, the regulation and use of stem cells in their research field. Finally, we select some articles for analysis, which conveyed information on advances in techniques for obtaining stem cells and we contrast the regimes of truth with regimes of hope present in the arguments presented by the media. Such media were understood as documents of public domain and were analyzed according to the concepts from the perspective of discursive practices. The media understood as discursive practices are important in the construction and circulation of repertoires in our society and, as language in action, always have consequences. Thus, the scientific mediation, as pointed out by Latour (1994), rather than as a simple diffusion, is endowed with the ability to translate what it carries; resetting it, breaking it down or even betraying it